All Hat and No Cattle? ESG Incentives in Executive Compensation - Matthias Efing; Stefanie Ehmann; Patrick Kampkötter; Raphael Moritz (CESifo GmbH, 2024)
This paper examines the integration of ESG performance metrics into executive compensation using a detailed panel dataset of European executives. Despite becoming more widespread, most ESG metrics are largely discretionary, carry immaterial weights in payout calculations, and contribute little to executive pay risk. Such ESG metrics with arguably weak incentive power are common in financial firms and large companies, particularly for their most visible executives, which seems consistent with greenwashing. In contrast, binding ESG metrics with significant weights, which have potential to influence incentives, are only found in sectors with a large environmental footprint.
Keywords: G30; G35; J33; M12; M52; 330; executive compensation; ESG; ESG metrics; ESG contracting; CSR contracting; sustainability; incentive contracting; optimal contracts